The impact of funding for public state universities in Mexico on the quality of education (Encuentros, 2024)
This research aims to centrally analyze the impact of state and federal public funding allocated to public state higher education institutions in Mexico on the performance of scientific research. Through the review of previous studies, international indicators, and government official data, a database of indicators was created for comparison and correlation. The findings presented highlight the importance of allocating adequate resources and contribute to the understanding of how funding can influence performance in scientific research, innovation, social impact, and, consequently, the continuous improvement of the quality of education in the universities under analysis. Finally, it provides recommendations to strengthen this link for the benefit of students and society.
Keywords: Quality education; Education; Higuer Education Institutions; Sustainable Development Goal 4 (SDG4)